BATIK MOTIFS MAPPING IN EAST JAVA AS LOCAL CULTURAL HERITAGE DOCUMENTATION - Ristya Rini, Denik (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Batik has a charm of beauty that is known by the people, both within and outside the country. UNESCO has recognized batik as a local indigenous cultural heritage of Indonesia. Almost all regions in Indonesia have a batik with the distinctive motifs of each region. The famous batik is Yogyakarta batik, Solo Batik, Cirebon Batik and Lasem Batik. Apart from some batik producing regions, East Java is also one of the areas that producing batik. Batik producing areas in East Java spread in several districts. Each region has its own color and motif. This makes East Java as an area that has a lot of diversity of batik motifs. One name of the same motif usually has the characteristic details of different motifs and staining on each region. Unfortunately, the diversity of batik motifs in East Java has not been mapped in detail in each region. This research was conducted to mapping batik motifs in East Java to be well documented as Indonesian cultural heritage.